(Critical Review) The State of Children during Pandemic: An Alarming Situation for Pakistan - Maryam Iftikhar; Komal Iftikhar (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2021)
Coronavirus and pandemics have led to drastic and unexpected changes in the whole world. It has affected people’s lives and their ways of living drastically. Although lockdowns and mobility restrictions were imposed to save lives, on the other hand, it put the lives of the underprivileged population at other risks too such as violence and abuse. This paper attempts to describe the situation of children during this epidemic of covid-19. Evidence and researches proved that emergency situations are significantly related to an increased level of violence, especially against children. A number of problems from which children suffered during pandemic and lockdown have been discussed such as excessive screen use, domestic child abuse, witnessing domestic violence, etc. Furthermore, this paper also suggests essential recommendations for not only the government but also for the public as they must corporate with the government in such high alert times.